Science in NASA's vision for space exploration (National Academies Press, 2005)
"In January 2004, President Bush announced a new space policy directed at human and robotic exploration of space. The National Academies released a report at the same time that independently addressed many of the issues contained in the new policy. In June, the President s Commission on Implementation of United States Space Exploration Policy issued a report recommending that NASA ask the National Research Council (NRC) to reevaluate space science priorities to take advantage of the exploration vision. Congress also directed the NRC to conduct a thorough review of the science NASA is proposing to undertake within the initiative. This report provides an initial response to those requests. It presents guiding principles for selecting science missions that enhance and support the exploration program. The report also presents findings and recommendations to help guide NASA s space exploration strategic planning activity. Separate NRC reviews will be carried out of strategic roadmaps that NASA is developing to implement the policy."--Publisher's website